2005
DOI: 10.1002/rcm.2032
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of gluten: mapping of the 1Bx7 glutenin subunit in Chinese Spring cultivar by matrix‐assisted laser desorption/ionization

Abstract: The verification of the cDNA-deduced sequence of the high molecular weight glutenin subunit 1Bx7 in Chinese Spring cultivar was achieved by direct matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOFMS) analysis of the tryptic fragments. The published sequence of the 1Bx7 subunit contains 5 Lys and 15 Arg residues but, due to the presence of three Arg-Pro bonds, which are generally resistant to cleavage by trypsin, or cleaved to a very limited extent by trypsin, 19 peptides c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…The deduced molec- ular masses were 85,782 Da (1Dx5 *t ) and 87,663 Da (1Dx5.1 *t ), which were consistent with those determined by MALDI-TOF-MS, and the differences were within the limits of experimental error in the mass range of HMW glutenin (Hickman et al 1995). This suggested that both subunits lacked extensive post-translational modifications, such as glycosylation and phosphorylation, as did other HMW-GSs analyzed by different proteome approaches (Cozzolino et al 2001;Cunsolo et al 2004;Alberghina et al 2005). The two novel subunit genes were deposited in the GenBank under accession nos.…”
Section: Identification Of Novel Hmw-gs In Ae Tauschii: Sds-page Anasupporting
confidence: 74%
“…The deduced molec- ular masses were 85,782 Da (1Dx5 *t ) and 87,663 Da (1Dx5.1 *t ), which were consistent with those determined by MALDI-TOF-MS, and the differences were within the limits of experimental error in the mass range of HMW glutenin (Hickman et al 1995). This suggested that both subunits lacked extensive post-translational modifications, such as glycosylation and phosphorylation, as did other HMW-GSs analyzed by different proteome approaches (Cozzolino et al 2001;Cunsolo et al 2004;Alberghina et al 2005). The two novel subunit genes were deposited in the GenBank under accession nos.…”
Section: Identification Of Novel Hmw-gs In Ae Tauschii: Sds-page Anasupporting
confidence: 74%
“…Electrospray mass spectrometry (ESI‐MS) and matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) MS have in part contributed to the assessment of gluten protein heterogeneity as well as the characterization of gliadins and glutenins. Previous studies have shown that MALDI‐TOF MS may allow molecular weight determination of purified HMW‐GS, which falls within the experimental error of those expected from the gene sequence 7–14. ESI‐MS, already applied to study a recombinant α‐gliadin,15 has been proved less suitable for HMW‐GS analysis, because of its scarce ionization efficiency.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, studies on the characterization of glutenins have greatly improved toward the understanding of structures and functions of HMW-GS. In particular, proteomic technology centered with matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry (MALDI-TOF-MS) has rapidly developed rapidly and become a powerful tool for identifying storage proteins (Alberghina et al 2005;Kussmann et al 1997;Muccilli et al 2005). Some recent investigations have focused on the tryptic peptide mapping of high molecular weight glutenin subunits (Cozzolino et al 2001), but little work on measuring accurate molecular weights of the intact HMW-GS within the mixture of HMW subunits has been reported.…”
Section: Introductionmentioning
confidence: 99%